Contrast-enhanced ultrasound in differential diagnosis of gallbladder cancer from xanthogranulomatous cholecystitis - ZHANG Daojian, ZHANG Dexiang, WANG Jiwen, LU Pinxiang, LIU Houbao, LIU Han (Waike lilun yu shijian, 2020)
Objective To evaluate the value of contrast-enhanced ultrasound (CEUS) in the preoperative diagnosis of gallbladder cancer (GBC) and xanthogranulomatous cholecystitis (XGC). Methods Eighty-one patients with GBC and with XGC in Department of General Surgery Zhongshan Hospital during 2016 and 2018 were analyzed retrospectively for comparing the accuracy of imaging examination to diagnose GBC and XGC between transabdominal ultrasound(TAUS) and CEUS. Results Thirty-nine patients with GBC and 42 patients with XGC diagnosed by pathological examination postope-ratively were recruited in this study. Radical surgery was done in 31 cases with GBC and palliative resection of gallbladder for the rest. The patients underwent both TAUS and CEUS preoperatively. The accuracy of CEUS in the assessment of patients with gallbladder disease (62/81, 76.5%) was higher than that of TAUS (43/81, 53.1%) (P=0.002) significantly. The accuracy of CEUS in the diagnosis of GBC (32/39, 82.1%) was significantly higher than TAUS (21/39, 53.8%), P=0.007. CEUS had sensitivity of 82.1% and positive predictive value of 72.7% and negative predictive value of 81.1%, which were significantly higher than those of TAUS, respectively. All the patients with XGC had cholecystectomy. Conclusions CEUS is a more effective approach for GBC with a promising diagnostic value than TAUS.